A pocket reference for psychiatrists - Jenkins, Susan C; Gibbs, Timothy P; Szymanski, Sally R (American Psychiatric Press, 1990)
This pocket-sized book is a compendium of tables and lists, designed to provide the clinician already familiar with psychiatry with information that is necessary in the daily practice of psychiatry, along with lists that the clinician might find useful as reminders in evaluation and treatment. The book is organized into sections on the psychiatric history, specialized interviews and assessments, psychology referrals, medical psychiatry, diagnostic procedures, psycho-pharmacology, chemical dependence and electro-convulsive therapy.
Keywords: Psychotropic Drugs; Mental Disorders; psychiatrie; psychotropní léky; duševní poruchy; psychofarmakologie